PrEP in substance abuse treatment: a qualitative study of treatment provider perspectives - Spector, Anya Y (Subst Abuse Treat Prev Policy, 2015)
OBJECTIVES: To examine substance abuse treatment providers’ views on engaging clients in Pre-exposure Prophylaxis (PrEP) care and research trials. METHODS: Thirty-six medical and counseling service providers in six New York City outpatient substance abuse treatment programs participated in semi-structured qualitative interviews. Thematic content analysis was conducted by three coders, independently. RESULTS: Providers’ perspectives toward PrEP were characterized by six salient themes: 1) Limited PrEP awareness. 2) Ambivalence about PrEP; 3) Perception of multiple challenges to delivery; 4) Uncertainty about clients’ ability to be adherent to medication; 5) Concerns about medication safety/side effects; and 6) Perception of multiple barriers to conducting clinical trials. CONCLUSIONS: Despite anticipated challenges, providers supported the introduction of PrEP in outpatient substance abuse treatment. Comprehensive training for providers is needed and should include PrEP eligibility criteria, strategies to support adherence and medication monitoring guidelines. Linkages between substance abuse treatment and primary care and/or enhancement of capacity within clinics to offer PrEP may help facilitate PrEP delivery. When conducting research in outpatient clinics, it is particularly important to protect client confidentiality.